PREVALENCE OF DEPRESSIVE SYMPTOMS IN INSTITUTIONALIZED ELDERLY IN A MUNICIPALITY IN THE INTERIOR OF THE STATE OF GOIÁS (CIPEEX, 2023)
The presence of depressive symptoms in the elderly, especially those residing in long-term care facilities (LTCFs), allows for an understanding of how the institutionalized environment, marked by physical inactivity, functional decline, loss of personal autonomy, and reflection on one's own death, can affect the mood and life and future perspective of these individuals. This study aims to investigate the prevalence of depressive symptoms in institutionalized elderly individuals in a municipality in the interior of the state of Goiás. This cross-sectional study was conducted in the only ILPI in the municipality of Rio Verde – GO. The study population consisted of the 100 elderly residents of the ILPI during the data collection period, and those over 60 years of age and with more than six months of institutionalization were included in the study, while those with a medical diagnosis of mental disorder recorded in their records were excluded. Sociodemographic, economic, general health, institutionalization, functional dependency (Functional Independence Measure), and depressive symptom assessment (15-item Geriatric Depression Scale) information were collected. It was observed that (n=9; 30.3%) of the evaluated elderly presented depressive symptoms, reflecting the need for significant attention to the mental well-being of this vulnerable population, such as early identification and appropriate treatment of these symptoms.
Keywords: Depressive symptoms; Long-Term Care Facility for the Elderly; Elderly Health